Hubungan Ibu Hamil Kekurangan Energi Kronik Dengan Kelahiran Bayi Berat Badan Lahir Rendah - Dwi Handayani Paramita Benny; Idah Ayu Wulandari; Sri Ariani, Ni Komang; Ni Wayan Sri Rahayuni; Ni Ketut Noriani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2024)
Pregnant women who have less nutritional intake adequately during pregnancy have the potential to experience chronic energy deficiency (CED) and tend to give birth to babies with low birth weight (LBW). One of the indicators used to determine chronic energy deficiency in mothers is upper arm circumference <23.5cm. The impact of LBW on children's growth is the occurrence of stunting. The purpose of this study was to determine the correlation between chronic energy deficiency and low birth weight babies at the Public Health Center Kambaniru, East Sumba. This study employed quantitative analysis with a cross-sectional approach. The sample was 29 respondents recruited from medical record data of pregnant women who gave birth to LBW babies. Data were analyzed using the Spearman's Rho correlation technique test. Findings indicated that the majority of 19 respondents (65.5%) with CED gave birth to children with LBW conditions, while 10 respondents (34.5%) without CED also gave birth to LBW babies. The Spearman's Rho test results indicated a significant positive correlation between mothers with CED and LBW babies. The lower the upper arm circumference of a pregnant woman, the higher the risk of giving birth to a LBW baby. It is expected that pregnant women will always carry out regular health checks during pregnancy and consume sufficient nutritious food.